Water hazard of mining and energy sector sin the context of climate change - López Muñoz, Cecilia (2016)
Peru is one of the most vulnerable countries to climate change. Even if the effects of this phenomenon are uncertain and unpredictable, but we can affirm that the increasing temperatures of the earth have impacts on the melting of glaciers and the alteration of the water cycle, in addition to its impact on extreme climate events and conflicts over water use. Even when it is stated that we are one of the richest in freshwater at regional level, the availability of this resource is uneven, and the coastal area represents the most demanding but the one that offers the least freshwater supply, generating a situation of pressure over water resources.This article has a very ambitious goal, since it aims to summarize the main implications of Climate Change in the availability of water for the mining and energy sectors, outlining some options for action in order to meet the challenge of a water crisis in our country.